Further delineation of dosage‐sensitive K/L mediated Xq28 duplication syndrome includes incomplete penetrance. Issue 6 (16th February 2023) - Leffler, Melanie; Christie, Louise; Hackett, Anna; Bennetts, Bruce; Goel, Himanshu; Amor, David J.; Peters, Greg B.; Field, Michael; Dudding‐Byth, Tracy
Abstract: The low copy tandem repeat area at Xq28 is prone to recurrent copy number gains, including the K/L mediated duplications of 300 kb size (herein described as the K/L mediated Xq28 duplication syndrome). We describe five families, including nine males with K/L mediated Xq28 duplications, some with regions of greater copy number variation (CNV). We summarise findings in 25 affected males reported to date. Within the five families, males were variably affected by seizures, intellectual disability, and neurological features; however, one male with a familial K/L mediated Xq28 duplication has normal intelligence, suggesting that this CNV is not 100% penetrant. Including our five families, 13 carrier females have been identified, with nine presenting phenotypically normal. Three carrier females reported mild learning difficulties, and all of them had duplications containing regions with at least four copies. Delineation of the spectrum of K/L mediated Xq28 duplication syndrome highlights GDI1 as the most likely candidate gene contributing to the phenotype. For patients identified with CNVs in this region, high‐resolution microarray is required to define copy number gains and provide families with accurate information. Abstract : The findings highlight a correlation between copy number gains of the GDI1 gene and disease severity and the importance high‐resolution microarray to define precise copy number gain. Non‐penetrance of the Xq28 K/L‐low copy number mediated Xq28 duplication is reported in one male.